Benthic mud content is a strong indicator of coral cover and ecosystem recovery on turbid coral reefs - Joppien, Marlena (2025)
Turbid coral reefs are characterised by high turbidity and sedimentation. However, the impacts of terrestrial sediment inputs on coral communities, as well as their interactions with reef-derived carbonate sediment, remain poorly understood. Here we examine the physical properties of mixed carbonate-siliciclastic benthic sediments from six turbid reefs in southern Singapore, which exhibit coral covers ranging from 15 % to 65 %. Coral was the dominant contributor to sand and gravel sediment on reefs (mean ± SE: 57 ± 1 %), followed by molluscan grains (21 ± 1 %). Mud content ranged from 0 to 26 % between sites and there was a positive correlation (r = 0.4) between terrigenous mud and coral-derived sand, while coral cover significantly decreased with increasing mud. Results suggest that losses in coral cover may initially cause an increase in bioclastic carbonate sediment as the reef structure degrades. However, long-term declines in coral cover will ultimately reduce sediment supply, as live coral sources diminish on reefs. Our findings highlight the importance of mitigating high sediment loads on coral reefs, even within naturally turbid environments, to ensure continued bioclastic sand generation and ecosystem functioning. Mud content on reefs was also a strong predictor of reef recovery following major coral bleaching underscoring the need for holistic transboundary management of coral reefs as coastal urbanisation continues to intensify.